The Effect of Board Size, Independent Board and Audit Committee, on Firm Value - Deflora Rita Ngadin; Sri Lestary Yuli Prastyantini (Journal of Social Growth and Development Studies, 2025)
Increasingly fierce business competition requires companies to increase company value to attract investors. One way that can be taken is to strengthen the implementation of Good Corporate Governance (GCG), especially through the role of the size of the board of directors, independent board, and audit committee. This study aims to analyse the effect of board size, independent board, and audit committee on firm value in financial sector service companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. This research method uses quantitative methods with secondary data obtained from the company's annual financial statements. The sampling technique used purposive sampling with a total of 13 companies as research samples. The data analysis technique used is multiple linear regression which is tested with the help of the SPSS version 25 programme. The results showed that board size has a positive and significant effect on firm value. The independent board also has a positive and significant effect on firm value. Meanwhile, the audit committee has no significant effect on firm value, although the regression coefficient shows a positive direction.